2008
DOI: 10.1016/j.jvs.2007.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Infected aneurysm of the thoracic aorta

Abstract: Infected aneurysm of the thoracic aorta was uncommon. The clinical results of in situ grafting were improving. Nontyphoid Salmonella was the most common responsible microorganism, and the prognosis of infection caused by Salmonella was not dismal. Outcomes of other management strategies, such as endovascular stenting, need to be compared with these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 29 publications
0
97
0
1
Order By: Relevance
“…22 Non-Salmonella-positive blood culture was the main factor associated with serious late complications in the present report, an observation supported by previous smaller reports. 8,19,26,27 The duration and choice of ABx-therapy is an important matter for debate. Some authors recommend parenteral or oral ABx for at least 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Non-Salmonella-positive blood culture was the main factor associated with serious late complications in the present report, an observation supported by previous smaller reports. 8,19,26,27 The duration and choice of ABx-therapy is an important matter for debate. Some authors recommend parenteral or oral ABx for at least 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in obtaining anaerobic cultures, and the fact that these patients often received early broad spectrum antibiotics, may explain the rate of positive cultures in the present report (67%), which is in line with previous reports on endovascular as well as on open repair. 6,7,27,28 Consequently, microbiological cultures (blood or aortic tissue) may turn out negative, despite a high clinical suspicion of a MAA. Adding to the complexity of this issue, routine culture of abdominal aortic aneurysm wall during open surgery of clinically noninfected patients has been found to be positive in ≈14% to 37% of the cases.…”
Section: Limitationsmentioning
confidence: 99%
“…Several studies in Taiwan, including our institutional experience, have demonstrated a graft infection rate of 8.0-10.4% after in situ prosthetic graft replacement for infected aortic aneurysms [11,12,[113][114][115][116]118]. In a more recent study investigating the outcomes of open repair of infected descending thoracic and thoracoabdominal aortic aneurysms by Lau et al, no postoperative graft infection occurred in 14 patients who had in situ prosthetic graft reconstruction [77].…”
Section: Choice Of Graft Materials For In Situ Reconstructionmentioning
confidence: 87%
“…When primary bacteremia is the cause, it most commonly originates from a distal infection in soft tissue or an infection in the lung, bone, or joint tissue. At the site of a preexisting aneurysm, the wall of the aorta is thinned and can be further weakened by focal acute and chronic inflammation; therefore, this site is as likely to develop into an infected pseudoaneurysm, as is its propensity to rupture (2)(3)(4)(5)(6)(7)10).…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate among patients with infected aortic aneurysms treated with antibiotics alone has been reported at 16% -44% (5,15). The critical points in the management of infected aortic aneurysm are the optimal timing of surgical procedure and the antibiotic strategy.…”
Section: Discussionmentioning
confidence: 99%